SIKAP DENGAN PERAN TENAGA KESEHATAN DALAM PELAKSANAAN INISIASIMENYUSU DINI (IMD) (Studi Di Wilayah Puskesmas Tembelang Dan Cukir Kabupaten Jombang) - Rivionita Citra Dewayani; . Muarrofah; Marxis Udaya (Jurnal Keperawatan, 2013)
Early Initiation of Breastfeedingis a programthat isissuedbyWHO/UNICEFin 2007, instead ofmotherswhobreastfeedinfants, but infantsshouldactivelyfindtheir ownmother's nipple. In sixdeveloping countriesthe riskof deathamonginfantsaged 9-12monthsincreased by40% ifthe babyisnot breastfed. Aimstodetermine therelationship ofattitudesto the role ofhealth workersin the implementationof earlyinitiationofbreastfeedinginRegionalHealth CenterandCukirTembelangJombang.This studyusesAnalyticaldesignwith crosssectional. The populationis30midwivesin primary healthcareand28midwivesin primary healthTembelang andCukir. The samplewas26midwivesin primary healthcareand25midwivesin primary healthTembelang and Cukirwithproportionalrandom samplingtechnique. Theindependent variableisthe attitude ofhealth workers(midwives) in the implementation ofearlybreastfeedinginitiationandthe dependentvariableisthe role ofhealth professionals(midwives) in theimplementation ofearly breastfeedinginitiation. Collecting datausing aquestionnaireandanalyzed byChi-Square test.The results showedthe role ofhealth workersin the implementation ofearly breastfeedinginitiationaremostlyactiveandattitude ofhealth workersin the implementation ofearly breastfeedinginitiationislargelypositive. The Chi-Square testresultsobtainedsignification at Pvalue<α (0.001 <0.05), then H0isrejectedandH1is accepted.The conclution of result is a relationshipattitudeto the role ofhealth workersin the implementationofearlyinitiation ofbreastfeeding. Negative attitudesandpassiverolesare at earlyinitiationofbreastfeedingmanagementactions. Institutionsoften holdpartiesshoulddirect monitoringoftheimplementation of theearlyinitiation ofbreastfeedingspaciousness, andthemidwifeexpectedactivelyinvolvedupdatingknowledgeand skills.Keywords: attitudes, rolesand initiation ofbreastfeeding